2004
DOI: 10.1081/ja-200034729
|View full text |Cite
|
Sign up to set email alerts
|

Employment, Employment-Related Problems, and Drug Use at Drug Court Entry

Abstract: The literature indicates that employment may be an important factor for retaining substance misusing clients in treatment. Given the link between employment problems and treatment retention for Drug Court clients, the current project builds upon the existing services provided by Drug Courts in order to develop and implement an innovative model that focuses on obtaining, maintaining, and upgrading employment for Drug Court participants. The purpose of this article is to (1) describe the employment intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…Focus group participants were asked to identify critical factors related to getting a job/obtaining a job, keeping a job/maintaining a job, and upgrading employment skills/getting a better job (see Leukefeld et al, 2004). Participants indicated that they had trouble balancing employment with the strict and rigorous drug court treatment regimen, especially Leukefeld et al clients with familial responsibilities.…”
Section: The Employment Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Focus group participants were asked to identify critical factors related to getting a job/obtaining a job, keeping a job/maintaining a job, and upgrading employment skills/getting a better job (see Leukefeld et al, 2004). Participants indicated that they had trouble balancing employment with the strict and rigorous drug court treatment regimen, especially Leukefeld et al clients with familial responsibilities.…”
Section: The Employment Interventionmentioning
confidence: 99%
“…Project participants were 500 clients (327 males and 173 females) who entered two Kentucky drug court programs (see Leukefeld et al, 2004, for a description of the baseline participants). Of the initial 500 participants who entered the project at baseline and were randomized into the employment intervention or the control group (drug court as usual), less than half worked full-time, with 3.7 jobs in the 5 years before entering drug court.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Criminal and employment history-Pretreatment criminal history has been found to be negatively associated with treatment completion (Knight, Logan, & Simpson, 2001) and positively associated with posttreatment substance use (Hubbard et al, 1989;Messina et al, 2000). Researchers have also found that employment is associated with higher rates of treatment retention (Vendetti, McRee, Miller, Christiansen, & Herrel, 2002) and lower rates of posttreatment use (Leukefeld, McDonald, Staton, & Mateyoke-Scrivner, 2004;Platt, 1995;Wolkstein & Spiller, 1998).…”
Section: Individual-level Controlsmentioning
confidence: 92%
“…In order to help participants regain control of their lives, an intensive component of this holistic approach involves addressing employment problems and assisting participants with acquiring and maintaining employment; in fact, diligent efforts to find employment and remain employed are requirements for retention in many drug court programs (Leukefeld, McDonald, Staton, & Mateyoke-Scrivner, 2004). Research shows that rates of substance abuse are highest among those who are unemployed (Townsend, Lane, Dewa, Brittingham, & Pergamit, 1999;Wilkinson, Leigh, Cordingley, Martin, & Lei, 1987).…”
Section: Transformation Of the Model For Child Welfare Interventionmentioning
confidence: 99%